The Cambridge handbook of expertise and expert performance - Ericsson, Karl Anders; Charness, Neil H.; Feltovich, Paul J.; Hoffman, Robert R. (Cambridge University Press, 2013)
Introduction and perspective -- An introduction to Cambridge handbook of expertise and expert performance : its development, organization, and content / K. Anders Ericsson -- Two approaches to the study of experts' characteristics / Michelene T.H. Chi -- Expertise, talent, and social encouragement / Earl Hunt -- Overview of approaches to the study of expertise : brief historical accounts of theories and methods -- Studies of expertise from psychological perspectives / Paul J. Feltovich, Michael J. Prietula & K. Anders Ericsson -- Educators and expertise : a brief history of theories and models / Ray J. Amirault & Robert K. Branson -- Expert systems : a perspective from computer science / Bruce G. Buchanan, Randall Davis, & Edward A. Feigenbaum -- Professionalization, scientific expertise, and elitism : a sociological perspective / Julia Evetts, Harald A. Mieg, & Ulrike Felt -- Methods for studying the structure of expertise -- Observation of work practices in natural settings / William J. Clancey -- Methods for studying the structure of expertise : psychometric approaches / Philip I. Ackerman and Margaret E. Beier -- Laboratory methods for assessing experts' and novices' knowledge / Michelene T.H. Chi -- Task analysis / Jan Maarten Schraagen -- Eliciting and representing the knowledge of experts / Robert R. Hoffman and Gavan Lintern -- Protocol analysis and expert thought : concurrent verbalizations of thinking during experts' performance on representative tasks / K. Anders Ericsson -- Simulation for performance and training / Paul Ward, A. Mark Williams & Peter A. Hancock -- Methods for studying the acquisition and maintenance of expertise -- Laboratory studies of training, skill acquisition, and retention of performance / Robert W. Proctor & Kim-Phuon L. Vu -- Retrospective interviews in the study of expertise and expert performance / Lauren A. Sosniak -- Time budgets, diaries and analyses of concurrent practice activities / Janice M. Deakin, Jean Cote & Andrew S. Harvey -- Historiometric methods / Dean Keith Simonton -- Professional domains / Robert Hoffman -- Expertise in medicine and surgery / Geoff Norman ... [et al.] -- Expertise and transportation / Francis T. Durso & Andrew R. Dattel -- Expertise in software design / Sabine Sonnentag, Cornelia Niessen & Judith Volmer -- Professional writing expertise / Ronald T. Kellogg -- Professional judgments and "naturalistic decision making" / Karol G. Ross, Jennifer L. Shafer, & Gary Klein -- Decision making expertise / J. Frank Yates & Michael D. Tschirhart -- The making of a dream team : when expert teams do best / Eduardo Salas ... [et al.] -- Arts, sports & motor skills -- Music / Andreas C. Lehmann & Hans Gruber -- Expert performance in sport : a cognitive perspective / Nicola J. Hodges, Janet I. Starkes & Clare MacMahon -- Artistic performance : acting, ballet, and contemporary dance / Helga Noice & Tony Noice -- Perceptual-motor expertise / David A. Rosenbaum ... [et al.] -- Games and other types of expertise -- Expertise in chess / Fernand Gobet & Neil Charness -- Exceptional memory / John M. Wilding & Elizabeth R. Valentine -- Mathematical expertise / Brian Butterworth -- Expertise in history / Jim F. Voss & Jennifer Wiley -- Generalizable mechanisms mediating expertise and general issues -- A merging theory of expertise and intelligence / John Horn & Hiromi Masunaga -- Tacit knowledge, practical intelligence and expertise / Anna T. Cianciolo ... [et al.] -- Expertise and situation awareness / Mica R. Endsley -- Brain changes in the development of expertise : neuroanatomical and neurophysiological evidence about skill-based adaptations / Nicole M. Hill & Walter Schneider -- The influence of experience and deliberate practice on the development of superior expert performance / K. Anders Ericsson -- Development and adaptation of expertise : the role of self-regulatory processes and beliefs / Barry J. Zimmerman -- Aging and expertise / Ralf Th. Krampe & Neil Charness -- Social and sociological factors in the development of expertise / Harald A. Mieg -- Modes of expertise in creative thinking : evidence from case studies / Robert W. Weisberg